A PRACTICE REVIEW: INNOVATIVE IDEAS FOR EXPANDING MULTILINGUAL ACCESS IN INFORMAL SCIENCE EDUCATION - Xinxin Wang (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This review examines the interactive experiences of multilingual visitors in science museums, with a focus on how these spaces can better serve visitors who face linguistic and cultural barriers. The author’s perspective is shaped by personal experiences as an international student from China and as an ESL educator in the U.S., offering valuable insight into the challenges faced by multilingual adults when navigating museum exhibits. Through a comprehensive analysis of current practices in science centers, the study identifies significant obstacles to access, including language barriers, limited multilingual resources, and a lack of cultural sensitivity in museum programming. The review also explores various strategies employed by museums in various subjects to address these barriers. These include the provision of multilingual audio guides, bilingual signage, and culturally relevant educational programs. The study draws attention to the need for science museums to rethink their approach to inclusivity, recognizing that the diversity of museum visitors is growing, with multilingual populations becoming a larger and more influential demographic. As part of this, the review considers examples from existing programs that have successfully engaged multilingual audiences, highlighting the potential for community-based science initiatives, digital resources, and collaborative partnerships with local cultural organizations. By analyzing both the barriers faced by multilingual visitors and the ongoing efforts to address these challenges, the research advocates for a systemic approach to inclusivity in science education. It emphasizes that science museums can and should be leaders in fostering equitable access to educational resources for all visitors, regardless of their language proficiency. Ultimately, the review aims to contribute to the ongoing dialogue about how science museums can evolve to reflect the multicultural and multilingual realities of contemporary society, fostering more inclusive, engaging, and educational environments for diverse audiences.